Perancangan Pemenuhan Persyaratan Sertifikasi ISO 9001:2015 Pada PT. Alam Jaya Seafood - Hendra Wijaya; Jani Rahardjo (Jurnal Titra, 2021)
PT Alam Jaya Seafood is a company that manufactures frozen food, especially seafood. PT. Alam Jaya Seafood is looking to expand the market into the international market especially the european market. Unfortuneately PT. Alam Jaya Seafood can’t penetrate the European market because they doesn’t have a quality assurance system. Two of the most common quality assurance system needed to enter is British Retail Consortium and ISO 9001:2015. ISO 9001:2015 is one of the qulity assurance that PT. Alam Jaya Seafood needed, therefore this thesis was conducted.  The Result of the initial gap analysis shows that PT. Alam Jaya Seafood fullfilled 37.5% of the clauses. After the fullfillment and implementation, pre-audit was conducted at the end of the thesis. The pre-audit shows that the fullfilment have increased to 81.25%. This Pre-Audit was conducted to prepare PT. Alam Jaya Seafood for the real audit that needed in order to achieve the certification.